PROSES AKUISISI SOFTWARE DI PT. MANULIFE INDONESIA - Revo Agri Muis; Sartika Wulansari; Richard Kumaradjaja (Bina Nusantara University, 2008)
Technology developments open the opportunity to develop faster and more capability in computing. These matters create the demand for new computing; especially demand for more capable application systems. Therefore, it is imperative for all organization to keep competitive and up to date systems. Ignoring these requirements leads toward reliance on application vendor, off which, by the time, will be obsolete and/or the vendor support will eventually be ceased to exist. Manulife Indonesia, one of the biggest insurance companies in Indonesia, has attempted to apply the right technology and the right strategy to support the Business objectives and strategies. Manulife Indonesia also has to apply up to date information technologies in order to support the business needs and to be the market leader in Indonesia. The purpose of this study is to identify whether information technologies management at Manulife Indonesia confirms with the one recommended by CobiT (Control Objective for Information and Related Company). CobiT aims to harmonize Business purposes and information technology purposes. This study, using Boston Market Theory, also attempts to identify market share and market growth of Manulife Indonesia in the Life Insurance industry in Indonesia, so that the technology implication of the market positions can be in line with Business purposes for strengthening the positions in the market.